Effect of a fifth round of seasonal malaria chemoprevention in children aged 5–14 years in Dangassa, an area of long transmission in Mali. (February 2023) - Konate, Drissa; Diawara, Sory I.; Sogoba, Nafomon; Shaffer, Jeff; Keita, Bourama; Cisse, Abdourhamane; Sanogo, Ibrahim; Dicko, Ilo; Guindo, Merepen dite Agnes; Balam, Saidou; Traore, Abdouramane; Kante, Salimata; et al.
Abstract: Despite a significant reduction in the burden of malaria in children under five years-old, the efficient implementation of seasonal malaria chemoprevention (SMC) at large scale remains a major concern in areas with long malaria transmission. Low coverage rate in the unattainable areas during the rainy season, a shift in the risk of malaria to older children and the rebound in malaria incidence after stopping drug administration are mainly reported in these areas. These gaps represent a major challenge in the efficient implementation of SMC measures. An open randomized study was conducted to assess the effect of a fifth additional round to current regime of SMC in older children living in Dangassa, a rural malaria endemic area. Poisson regression Model was used to estimate the reduction in malaria incidence in the intervention group compared to the control group including age groups (5–9 and 10–14 years) and the use of long-lasting insecticidal nets (LLINs; Yes or No) with a threshold at 5%. Overall, a downward trend in participation rate was observed from August (94.3%) to November (87.2%). In November (round 4), the risk of malaria incidence was similar in both groups (IRR = 0.66, 95%CI [0.35–1.22]). In December (round 5), a decrease of 51% in malaria incidence was observed in intervention group compared to control group adjusted for age groups and the use of LLINs (IRR = 0.49, 95%CI [0.26–0.94]), of which 17% of reduction is attributable to the 5th round in the intervention group. An additional fifth round of SMC resulted in a significant reduction of malaria incidence in the intervention group. The number of SMC rounds could be adapted to the local condition of malaria transmission.